Science Module Development Problem-Based Learning for Biodiversity in Junior High School - Corneli Pary; Fatma Keliata; Janaba Renngiwur; Tri Santi Kurnia (Postgraduate, University of Mataram, 2025)
This study aims to develop a problem-based science learning module in biodiversity material for grade VII students of SMP Muhammadiyah Ambon. This research uses a 4-D development model from Thiagarajan, which consists of the stages of defining, designing, and developing. This study was conducted by involving 25 seventh grade students as a research sample at SMP Muhammadiyah Ambon. Data was collected through module validation, practicality questionnaires, and effectiveness questionnaires. The results showed that the modules developed were very valid, with a percentage of validation from material experts of 88%, media aspects of 85%, and language aspects of 80%. The practicality test shows that this module is very practical, reaching a percentage of 97%. Meanwhile, student responses to modules and learning activities showed a high level of effectiveness, with an average total response of 93.29%. Post-test results also showed a high level of effectiveness, with a percentage of 84%. Also indicated by a greater n-gain value equal to 0.8 in the high category. Based on the results of this study, it can be concluded that the problem-based science learning module on biodiversity material for grade VII students at SMP Muhammadiyah Ambon is suitable for use in the learning process.